Subchronic Systemic Toxicity of New Endodontic Material Based on Calcium Hydroxyapatite and Calcium Silicates - Vukoman Jokanović; Božana Čolović; Bogomir Bolka Prokić; Nada Tomanović; Marijana Popović Bajić; Slavoljub Živković (Advances in Materials Science and Engineering)
As an alternative to MTA, a new endodontic material based on hydroxyapatite and calcium silicates (ALBO-MPSA) has been synthesized, and its biocompatibility has been studied in many in vitro and in vivo studies. The current study aims to evaluate a subchronic systemic toxicity of ALBO-MPSA on the rat animal model, as a continuation of the previous studies. Biochemical parameters of blood and histological parameters of the liver, kidneys, and spleen of the rats were analyzed after 120 days of consumption of the aqueous extract of ALBO-MPSA. The results showed no myelotoxic effect or autoimmune effect on peripheral blood cells and no pathological effect on the liver, kidney, and spleen tissues. Besides, no changes in the skin and hair of the rats, neither the change in the consumption of food and water, nor the change in their usual behavior were noticed during the experiment.